Study of Preference for Surround Microphone Techniques Used in the Recording of Choir and Instrumental Ensemble - SITEK, Andrzej; KOSTEK, Bożena (Archives of Acoustics, 2011)
The aim of this paper is to describe the process of choosing the best surround microphone technique for recording of choir with an instrumental ensemble. First, examples of multichannel microphone techniques including those used in the recording are described. Then, the assumptions and details of music recording in Radio Gdansk Studio are provided as well as the process of mixing of the multichannel recording. The extensive subjective tests were performed employing a group of sound engineers and students in order to find the most preferable recording techniques. Because the final recording is based on the mix of “direct/ambient” and “direct-sound all-around” approaches, a subjective quality evaluation was conducted and on this basis the best rated multichannel techniques were chosen. The results show that listeners might consider different factors when choosing the best rated multichannel techniques in separate tasks, as different systems were chosen in the two tests.